A Review of Clinical Outcomes for Gait and Other Variables in the Surgical Treatment of Idiopathic Normal Pressure Hydrocephalus. Issue 4 (18th February 2016) - Shaw, Richard; Mahant, Neil; Jacobson, Erica; Owler, Brian
Abstract: Background: Idiopathic normal pressure hydrocephalus (INPH) is a treatable cause of gait disturbance, cognitive impairment, and urinary incontinence. This clinical triad of symptoms occurs in association with ventriculomegaly and normal cerebrospinal fluid (CSF) pressure. Although the treatment outcomes after CSF shunting for INPH have improved significantly since its first description in 1965, shortcomings in our understanding still remain. Not all INPH patients exhibit clinical improvement after shunting, and it is challenging to identify patients who are more likely to benefit from shunting. Methods: The Cochrane Library, Medline, Embase, and PubMed databases were searched for English‐language publications between 1965 and October 2015. Reference lists of publications were also manually searched for additional publications. Results: The findings of this review indicate that, despite efforts to improve patient selection, the degree of clinical improvement after shunting continues to demonstrate significant variability both within and between studies. These discrepancies in treatment outcomes are the result of controversies in 3 distinct but interrelated domains: the underlying pathophysiology of INPH, the diagnosis of INPH, and the identification of likely shunt‐responders. Conclusions: This review focuses on these 3 areas and their relation to surgical treatment outcomes. Despite the limitations of published outcome studies and limitations in our understanding of INPH pathophysiology, shunting is a safe and effective means of achieving meaningful clinical improvement in most patients with INPH.